Childhood Craniopharyngioma – Changes of Treatment Strategies in the Trials KRANIOPHARYNGEOM 2000/2007 - Hoffmann, A.; Warmth-Metz, M.; Gebhardt, U.; Pietsch, T.; Pohl, F.; Kortmann, R.-D.; Calaminus, G.; Müller, H. L. (Klinische Pädiatrie, 2014)
Background: Prognosis in childhood craniopharyngioma, is frequently impaired due to sequelae. Radical surgery was the treatment of choice for decades. Even at experienced facilities radical surgery can result in hypothalamic disorders such as severe obesity.Objective: We analyzed, whether treatment strategies for childhood craniopharyngioma patients recruited in GPOH studies have changed during the last 12 years.Materials and methods: We compared the grade of pre-surgical hypothalamic involvement, treatment, degree of resection and grade of surgical hypothalamic lesions between patients recruited in KRANIOPHARYNGEOM 2000 (n=120; 2001–2007) and KRANIOPHARYNGEOM 2007 (n=106; 2007–2012).Results: The grade of initial hypothalamic involvement was similar in patients treated 2001–2007 and 2007–2012. The realized treatment was more radical (p=0.01) in patients recruited 2001–2007 (38%) when compared with patients treated 2007–2012 (18%). In patients with pre-surgical involvement of anterior/posterior hypothalamic areas, the rate of hypothalamus-sparing operations resulting in no (further) hypothalamic lesions was higher (p=0.005) in patients treated 2007–2012 (35%) in comparison with the 2001–2007 cohort (13%). Event-free-survival rates were similar in both cohorts.Conclusions: A trend towards less radical surgical approaches is observed, which was accompanied by a reduced rate of severe hypothalamic lesions. Radical surgery is not an appropriate treatment strategy in patients with hypothalamic involvement. Despite previous recommendations to centralize treatment at specialized centers, a trend towards further decentralization was seen.
Keywords: craniopharyngioma; hypothalamus; obesity; quality of life; pediatrics; neurooncology